APRIL: A double-blind, placebo-controlled, randomized, Phase Ib/IIa clinical study of ApTOLL for the treatment of acute ischemic stroke - Hernández-Jiménez, Macarena; Abad-Santos, Francisco; Cotgreave, Ian; Gallego, Jaime; Jilma, Bernd; Flores, Alan; Jovin, Tudor G.; Vivancos, José; Molina, Carlos A.; Montaner, Joan; Casariego, Joaquín; Dalsgaard, Mads; et al. (Frontiers in Neurology, 2023)
In the reperfusion era, a new paradigm of treating patients with endovascular treatment (EVT) plus neuroprotective drugs is emerging as a promising therapeutic option for acute ischemic stroke (AIS) patients. In this context, ApTOLL, a Toll-like receptor 4 (TLR4) antagonist with proven neuroprotective effect in preclinical models of stroke and a very good pharmacokinetic and safety profile in healthy volunteers, is a promising first-in-class aptamer with potential to address this huge unmet need. This protocol establishes the clinical trial procedures to conduct a Phase Ib/IIa clinical study (APRIL) to assess ApTOLL tolerability, safety, pharmacokinetics and biological effect in AIS patients who are eligible for EVT. This will be a multicenter, double-blind, randomized, placebo-controlled, Phase Ib/IIa clinical study to evaluate the administration of ApTOLL together with EVT in AIS patients. The study population will be composed of men and non-pregnant women with confirmed AIS with a <6h window from symptoms onset to ApTOLL/placebo administration. The trial is currently being conducted and is divided in two parts: Phase Ib and Phase IIa. In Phase Ib, 32 patients will be allocated in four dose ascending levels to select, based on safety criteria, the best two doses to be administered in the following Phase IIa in which 119 patients will be randomized to three arms of treatment (dose A, dose B and placebo).